Ciencia y técnica en la anticiencia: ficción de C.S. Lewis. (2011)
The article analyzes the image of Western science and technology (and by extension of civilization in which they are prominent); that put CS Lewis s Cosmic Trilogy (classic of fantasy literature and religion of the twentieth century). In the scientific-technical culture now prevailing in these three novels; Lewis proposes a civilization rooted in Christianity. Faced with a scientific-technical culture to promote the dehumanization just the discrimination of humans and nonhumans; new forms of alienation and; ultimately; opposed to wisdom; Lewis bet the alternative of a return to Christ. Such a return to Christ is also the return to wisdom; and thus opting for a path leading to full humanization